INCOME ANALYSIS OF ARECA NUT (Areca Catechu) FARMING IN ULEE LHAT VILLAGE MONTASIK SUBDISTRICTACEH BESAR DISTRICT: ANALISIS PENDAPATAN USAHATANI PINANG (Areca catechu) DI DESA ULEE LHAT KECAMATAN MONTASIK KABUPATEN ACEH BESAR - Keumalasari, Sofia; Mulyanti; Nurul Khalisah; Umar Husein Abdullah (ROCE : Jurnal Pertanian Terapan, 2025)
Areca nut (Areca catechu) farming is one of the agricultural sectors that has the potential to make an economic contribution to the community in Ulee Lhat Village, Montasik District, Aceh Besar Regency.  This study aims to analyze the income, profit, and farming efficiency of areca nut farmers. The research method used is a quantitative approach with data collection through surveys and interviews with areca nut farmers. Analysis was carried out using the farm feasibility analysis method. The results showed that the income of areca farming in Ulee Lhat Village, Montasik District was Rp 971,850. An R/C efficiency of 2.50, means that the total efficiency of areca nut farmers is feasible to cultivate because R/C> 1.